The Role of School Learning Communities in Building a Continuous Learning Culture and Increasing Teacher Professionalism - Kurniyawati, Yuli; Pramono, Suwito Eko; Sugi, Sugi (Proceedings of International Conference on Science, Education, and Technology, 2024)
Global demands and developments in science and technology have an impact on various sectors. Educational institutions also need to be supported by teachers who have 21st-century competencies and skills. One of the competencies that supports improving the quality of learning is professional competency. The ineffectiveness of learning communities in schools so far, of course, has an impact on the efficiency and effectiveness of achieving school goals. This paper aims to describe the role of school learning communities in building a culture of continuous learning and increasing teacher professionalism. The method used is an exploratory study that combines findings from various relevant sources complemented by interviews and direct observations in schools implementing the independent curriculum. The research results show that: (1) the school learning community is a forum that encourages teachers to collaborate, share good practices, and cultivate a culture of continuous learning. (2) The school learning community learns together and shares good practices with cycles of initial reflection, planning, implementation, and evaluation. (3) The learning cycle in the school learning community ensures that learning outcomes are implemented in learning, there is continuous improvement in learning so that professionalism increases.